Improving the Proteome-Mining of Schizophyllum commune to Enhance Medicinal Mushroom Applications - Anthea Desiderio; Lorenzo Goppa; Carlo Santambrogio; Stefania Brocca; Simone Buratti; Carolina Elena Girometta; Meghma Sarkar; Maria Teresa Venuti; Elena Savino; Paola Rossi; Emanuele Ferrari (Journal of Fungi, 2025)
This study presents the first comprehensive proteomic profile of an Italian strain of Schizophyllum commune, a highly heterogeneous white-rot fungal species with significant potential for industrial, nutraceutical, cosmeceutical, and clinical applications. Three protein extraction methods and their impact on yield and resulting protein composition have been compared. Results revealed that the combination of Tris–Cl and urea increases the total protein yield and the variety of enzymatic species related to pivotal pathways. Notably, over 2000 proteins were identified, including enzymes involved in the growth and development of mycelium, trehalose biosynthesis, and different types of carbohydrate-active enzymes (CAZymes). These enzymes are crucial for nutraceutical and agro-industrial applications of S. commune. The multiple-step proteomic approach used could be a model for investigating other fungal species.